2010 IEEE International Symposium on Information Theory 2010
DOI: 10.1109/isit.2010.5513739
|View full text |Cite
|
Sign up to set email alerts
|

An algebraic approach to physical-layer network coding

Abstract: This dissertation studies a family of the state-of-the-art PNC schemes called compute-and-forward (C&F). C&F was originally proposed and studied from an information-theoretic perspective. As such, it typically relies on several strong assumptions: very long block length, almost unbounded complexity, perfect channel state information, and no decoding errors at the relays; its benefit is often analyzed for simple network configurations. The aim of this dissertation is two-fold: first, to relax the above assumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
202
0
24

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(228 citation statements)
references
References 60 publications
2
202
0
24
Order By: Relevance
“…Also, µ(L, P e ) is the normalized volume-to-noise ratio (which is closely related to the coding gain) for a given error probability P e in nearest neighbor decoding of the lattice L. Note that (22) and (23) apply to an arbitrary lattice code instead of asymptotically-good lattice codes, where log (2πeG(L ′ )) and log…”
Section: Symmetric Mpr Csma Vs Conventional Csmamentioning
confidence: 99%
See 1 more Smart Citation
“…Also, µ(L, P e ) is the normalized volume-to-noise ratio (which is closely related to the coding gain) for a given error probability P e in nearest neighbor decoding of the lattice L. Note that (22) and (23) apply to an arbitrary lattice code instead of asymptotically-good lattice codes, where log (2πeG(L ′ )) and log…”
Section: Symmetric Mpr Csma Vs Conventional Csmamentioning
confidence: 99%
“…As a new MPR technique, C&F enables a receiver to recover simultaneously transmitted packets via decoding linear equations [17][18][19][20][21][22]. Compared to other MPR techniques, C&F achieves close-to-optimal performance [23,24] under single-user decoding, making it particularly attractive for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…In order to compare with the existent schemes, the baseline lattice network coding (LNC) scheme, which is used to practically implement CF in [3], is considered. To make a fair comparison, we have adjusted the power of the transmitters in the schemes with and without precoding, such that the total power available at the transmitters in both schemes is equal.…”
Section: Probability Of Error At the Relaymentioning
confidence: 99%
“…They have shown that the degrees of freedom (DoF) achievable by the lattice-based implementation of CF is at most two, when the channel gains are irrational. This is due to the gap between the natural channel gains and the integer coefficient of the linear combination in coherence to the observation in [3]. Further, it is proved that this limitation is not inherent to the fundamental concept of CF, but is due to the lattice-based implementation of CF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation